Management of healthcare waste in a small hospital - Castro, Révia Ribeiro; Guimarães, Otaciano Sales; Lima, Valdênia Maria Leandro de; Lopes, Conceição Delne Freitas; Chaves, Emília Soares (Rev Rene, 2014)
It aimed to conduct a situational analysis of the production and management of waste generated in a small hospital in the interior of the state of Ceará, Brazil, in 2014. Data collection occurred through systematic observation using checklist to verify routine procedures and questionnaires applied with the manager and employees responsible for hospital sectors. In the waste, it were found biological materials, anatomical parts, product of fertilization without vital signs, laboratory samples leftovers, containers and materials resultingfrom the health care process, chemical, household and sharps waste. It was verified improperly discarded waste according to current regulations. It is concluded the need for information and training of professionals who handle and dispose of healthcare waste.